Nitrous Oxide Emissions from an Alpine Grassland as Affected by Nitrogen Addition - Yufeng Wu; Xiaopeng Gao; Dengchao Cao; Lei Li; Xiangyi Li; Fanjiang Zeng (Atmosphere, 2021)
Nitrogen (N) addition is an important nutrient strategy for alpine grassland in northwestern China to improve productivity for livestock needs. A field experiment was conducted in a semi-arid alpine grassland in northwestern China to investigate the effect of N addition rates on soil N2O emissions over the growing seasons of 2017 and 2018. Treatments included six N addition rates (0, 10, 30, 60, 120, 240 kg N ha−1 y−1), which were applied before each growing season. The N2O fluxes increased with N addition rates and showed different episodic changes between the two growing seasons. In 2017, the maximum N2O flux rate occurred within 2 weeks following N addition. In 2018, however, the maximum N2O flux rate occurred later in the growing season due to a heavy rainfall event. Growing season cumulative N2O emissions ranged between 0.32 and 1.11 kg N ha−1, and increased linearly with N addition rates. Increasing N addition rates over 60 kg N ha−1 yr−1 did not further increase plant above-ground biomass. The inter-annual variability of N2O flux suggests the importance of soil moisture in affecting N2O emissions. It is particularly important to avoid over-applying N nutrients beyond plant needs to reduce its negative effect on the environment while maintaining livestock productivity. The N2O flux rate increased with soil dissolved organic carbon (DOC) and soil pH. These results suggest the optimal N addition rate to the livestock grassland in this region should be 60 kg N ha−1 yr−1.